Methods of test for orthoboric acid (boric acid), diboron trioxide (boric oxide), disodium tetraborates, sodium perborates and crude sodium borates for industrial use. Determination of iron soluble in alkaline medium in crude sodium borates Part 19, (28th February 1979) - British Standards Institution,
No abstract available